Manipulation of skyrmion motion by magnetic field gradients - S. L. Zhang (Nature Portfolio, 2018)
Manipulation of skyrmions is one of the keys to achieving the skyrmion based spintronic devices. Here the authors show the skyrmions in Cu2OSeO3 can be rotated collectively with fixed velocity–radius relationship under a static magnetic field gradient which enables a local, Joule heat-free control of skyrmions.